Kajian Kebutuhan Alat Berat pada Pekerjaan Tanah Pembangunan Turap atau Pematangan Lahan Parkir Kecamatan Pelayangan Seberang Kota Jambi - Annisaa Dwiretnani; Ilham Alfhito Putra (Universitas Batanghari Jambi, 2019)
Heavy equipment commonly used in construction projects are Dump trucks, excavators, dozers, soil compactors such as rollers and compactors. The purpose of using these heavy equipment is to make it easier for people to do the work so that the expected results can be achieved more easily in a relatively shorter time and as a reference to find out the needs of the equipment used in the work location whether or not they are needed (Aoliya, 2017). In the pavement / ripening development project Pelayangan sub-district parking lot across the city of Jambi the heavy equipment used is; excavators, dump trucks and dozers. The project which began in June 2017 was completed in December 2017. Based on observations of researchers in the field for the use of 2 (two) pieces of excavator used, 1 (one) dozer, and 20 (twenty) dump trucks. The use of heavy equipment used in the field is not yet known optimal productivity. An analysis of the calculation of the needs of heavy equipment is needed in the construction project of the pavement / ripening of the parking area of Pelayangan Seberang Subdistrict, Jambi City. This study consists of several stages, namely calculating the production capacity of each heavy equipment, calculating the value of productivity, then calculating the number of each tool needed, and in the final stage comparing the number of tools analyzed according to calculations with the number of tools in the field.